2016
DOI: 10.1371/journal.pone.0157311
|View full text |Cite
|
Sign up to set email alerts
|

Combined B, T and NK Cell Deficiency Accelerates Atherosclerosis in BALB/c Mice

Abstract: This study focused on the unique properties of both the Ldlr knockout defect (closely mimicking the human situation) and the BALB/c (C) inbred mouse strain (Th-2 slanted immune response). We generated two immunodeficient strains with severe combined B- and T-cell immunodeficiency with or without a complete lack of natural killer cells to revisit the role of adaptive immune responses on atherogenesis. C-Ldlr-/- Rag1-/- mice, which show severe combined B- and T-cell immunodeficiency and C-Ldlr-/- Rag1-/- Il2rg-/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Cheng et al showed that combined B, T, and NK cell deficiency accelerates atherosclerosis in BALB/c mice, demonstrating the impact of lymphocytes, including NKs, on lipoprotein metabolism along with the relevant contribution of lymphocyte subsets in plaque composition in atherosclerosis [101]. …”
Section: Natural Killer Cells In Atherosclerosismentioning
confidence: 99%
“…Cheng et al showed that combined B, T, and NK cell deficiency accelerates atherosclerosis in BALB/c mice, demonstrating the impact of lymphocytes, including NKs, on lipoprotein metabolism along with the relevant contribution of lymphocyte subsets in plaque composition in atherosclerosis [101]. …”
Section: Natural Killer Cells In Atherosclerosismentioning
confidence: 99%
“…ATS represents the most common pathophysiological alteration leading to ischemic heart disease and stroke ( 55 ). NK cells have been detected in atherosclerotic lesions in humans ( 56 , 57 ) and mice ( 32 , 33 , 58 , 59 ), mostly in advanced lesions, deep within plaques, and in shoulder regions of plaque ( 32 ). In addition, patients with advanced lesions show high levels of circulating NK cells ( 60 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the body releases hormones like catecholamines that regulate inflammatory substance levels in the blood, resulting in a decreased lymphocyte count. In ACS patients, stress and other factors can reduce lymphocyte levels in the plasma, significantly decreasing the CD4/CD8 ratio, weakening immune function, and inducing a short-term inflammatory state [ 22 ]. This contributes to arterial sclerosis development.…”
Section: Discussionmentioning
confidence: 99%